O mapeamento da pobreza e da cobertura dos programas governamentais nos municípios do Estado do Ceará - Melo Filho, Alberto de Souza (2012)
Using data from the IBGE, IPECE, IPEA and SEPLAG, this study provides a profile of poverty mapping, the distribution of resources from social programs FECOP - State Fund to Combat Poverty Program (Program of the Government of the State of Ceará) and Bolsa Família Program (Program of the Federal Government) in Ceará municipalities in 2010. The relationship between poverty levels and coverage of social programs are analyzed using Municipal Coverage Ratios and global statistics of efficiency in resource distribution of these programs. Regarding the first, by mapping the coverage of programs to combat poverty it was found the presence of a cluster in favor of the municipalities located on the east coast and region of Jaguaribana, especially for the Bolsa Família Program. The second analysis showed that the distribution of funds from Bolsa Família Program is performed more efficiently than the FECOP program. However, when using some control variables we observed that both programs work with equivalent efficiency.